Correlation of the size of self-assembled silver nanoparticles in phosphate glasses modified with aluminum or zinc oxides in RAMAN-SERS signal aiming application as early biomarker-related disease diagnosis - Ferreira, Kissia Batista (2020)
Dissertação (mestrado)—Universidade de Brasília, Instituto de Ciências Biológicas, Pós-Graduação em Nanociência e Nanobiotecnologia, 2020.